Mathematical Modelling of Impulse Excitation of a Superwideband PEC Cone Antenna - Doroshenko, V. O.; Klimova, N. P.; Stognii, N. P.; Kostyn, Yu. D. (2019 IEEE 8th International Conference on Advanced Optoelectronics and Lasers, CAOL*2019, 2019)
The method for solving initial-boundary electromagnetic problems is proposed. It uses the Green’s function method and the Laplace and Meler-Fock integral transforms in a time domain. The model problem of special slotted cone antenna excitation is studied. Integral and series representation of electromagnetic field component are given.
Keywords: initial boundary; cone; antenna; integral transform; approximations